The Effect of Allowances, Work Bonuses and Performance Improvements on Employee Loyalty: Pengaruh Tunjangan, Bonus Kerja dan Peningkatan Kinerja Terhadap Loyalitas Kerja Karyawan - Chusna, Nisaul; Kusuma, Kumara Adji (Indonesian Journal of Innovation Studies, 2022)
This study aims to determine the effect of allowances, work bonuses and performance improvements on employee work loyalty at PT. Sinerga Lintas Indonesia, either partially or simultaneously whether they affect employee work loyalty at PT. Sinerga Lintas Indonesia. And describe the benefits, work bonuses and performance improvements. The approach method in this research is a quantitative approach. Data was collected by distributing questionnaires, observations, and interviews as data reinforcement. The sampling technique in this study uses a total sampling technique to take a sample of all members of the population being sampled. According to Sugiyono (2018), the quantitative approach is a research approach used to measure the variables and the level of influence between one variable and another. Based on the results of the study, allowances, work bonuses and increased performance have a significant effect on work loyalty. Bonus is an employee’s right to the labor and services provided to the company. Employee performance improvement is an employee who has a high commitment to the company tends to show good quality, more totality in work and the employee turnover rate for the company is also low.